Enterobacter wuhouensis sp. nov. and Enterobacter quasihormaechei sp. nov. recovered from human sputum. Issue 2 (8th November 2019) - Wang, Chengcheng; Wu, Wenjing; Wei, Li; Feng, Yu; Kang, Mei; Xie, Yi; Zong, Zhiyong
Abstract : Two novel strains of members of the genus Enterobacter, WCHEs120002 T and WCHEs120003 T, were recovered from the sputum of two patients at a hospital in PR China in 2017. The strains were Gram-stain-negative, facultatively anaerobic, motile and non-spore-forming. The two strains were subjected to whole-genome sequencing. Phylogenetic analysis based on core genes of type strains of species of the family Enterobacteriaceae revealed that the two strains belonged to the genus Enterobacte r but were distinct from any previously known species of the genus. Both average nucleotide identity and in silico DNA–DNA hybridization values between strains WCHEs120002 T and WCHEs120003 T and type strains of all known species of the genus Enterobacter were lower than the recommended thresholds of 95 and 70  %, respectively, for species delineation. The major fatty acids of the two strains were C16 : 0, C17 : 0 cyclo and C18:1 ω7 c, which are similar to those of other species of the genus Enterobacter . Genomic DNA G+C contents of strains WCHEs120002 T and WCHEs120003 T were 56.09 and 55.91 mol%, respectively. WCHEs120002 T ferments melibiose and sucrose but is negative for d -sorbitol and methyl-α-d -mannopyranoside reactions, which distinguish it from all other species of the genus Enterobacter . WCHEs120003 T can be differentiated from other species of the genus Enterobacter by its ability to ferment potassium gluconate and its negative reactions for d -sorbitol and l -fucose. Genotypic and phenotypic characteristics indicate that strains WCHEs120002 T and WCHEs120003 T represent two novel species of the genus Enterobacter, for which the names Enterobacter wuhouensis sp. nov. and Enterobacter quasihormaechei sp. nov. are proposed, respectively. The type strain of E. wuhouensis sp. nov. is WCHEs120002 T (=GDMCC1.1569 T =NCTC 14273 T ) and the type strain of E. quasihormaechei sp. nov. is WCHEs120003 T (=GDMCC1.1568 T =NCTC 14274 T ).